Deinstitutionalising Meritocratic Plausibility Structures through Redignification of Ordinary Life - Gooch, Griffin Kennelly (International journal of public theology, 2025)
According to recent sociological analyses, the bottom fourth of the American income bracket is ‘dechurching’ faster and in larger numbers than any other demographic. Many factors play into this exodus: it is my belief that the West’s contemporary strain of meritocracy, which imbues those who succeed with a hubris and those who fail with humiliation, is the primary culprit for this alienation. The plausibility structures of upward social mobility cause winners to attribute their success to their hard work alone, while the losers attribute failure to their own lack of hard work. This prevailing framework implicitly embeds itself within ecclesial orthopraxy. In order to deinstitutionalise these deeply ingrained beliefs, meritocratic hubris should be countered by a redignification of all varieties of work, pedigree, and social position. This article argues that the ecclesial context is the ideal axiom for deconstructing plausibility structures that broadcast the universal accessibility of upward social mobility within Western society.